A Current Review of Edible Pickering Emulsion-Based Delivery Systems to Enhance Stability and Bioaccessibility of Lipophilic Bioactive Compounds - Arancibia-Aguilar, C; Alarcon-Moyano, J; Riquelme-Hinojosa, N (Taylor and Francis Ltd., 2025)
Lipophilic bioactive compounds present in food are susceptible to degradation during processing, storage, and transit through the gastrointestinal tract. Moreover, the solubility and bioaccessibility of these bioactive compounds is low. Emulsion-based delivery systems can improve these labile compounds’ stability, solubility, and release during digestion. In this regard, Pickering emulsions have gained significant attention in food science as a novel and promising approach for enhancing the stability and delivery of lipophilic bioactive compounds. These emulsions, stabilized by colloidal particles at the interface, provide a robust system for protecting encapsulated compounds and enhancing their bioaccessibility, and consequently their bioavailability. Therefore, this review provides an overview of recent advances in the application of Pickering emulsions for encapsulating bioactive compounds, emphasizing their beneficial properties and potential for enhancing stability and release during gastrointestinal digestion. This work also explores the key factors influencing the interfacial and stimuli-responsiveness properties of Pickering stabilizers for bioactive encapsulation in O/W emulsions. Finally, this review provides a detailed discussion of how Pickering emulsions can address challenges related to bioactive compound delivery in the food industry. It provides an in-depth analysis of current advancements and future potential, highlights the key challenges in this field, and identifies emerging research opportunities. © 2025 Taylor & Francis Group, LLC.